Who takes the trip? Personality and hallucinogen use among college students and adolescents. (1st December 2020) - Parnes, Jamie E.; Kentopp, Shane D.; Conner, Bradley T.; Rebecca, Rachel A.
Highlights: Impulsivity, sensation seeking, and emotion dysregulation predicted hallucinogen use. Inpatient adolescent's use was related to risk seeking, premeditation, and impulsivity. These relations varied between college students and inpatient adolescents. Abstract: Research examining hallucinogen use has identified potential benefits, as well as potential harms, associated with use. The acute effects of hallucinogen use can be intense, disorienting, cognitively impairing, and may result in perceptual changes mimicking aspects of temporary psychosis. Hallucinogen use may also lead to the onset of more chronic issues, such as Hallucinogen Persisting Perception Disorder, which impairs daily functioning even when sober. However, research on factors that predict who will misuse hallucinogens is an understudied area. In particular, while sensation seeking, impulsivity, and emotion dysregulation have all been shown to be predictive of problematic substance misuse, there is almost no research on how these personality variables predict hallucinogen use. The present study assessed how these personality traits predicted hallucinogen use in a sample of college undergraduates ( N = 10, 251) and a sample of adolescents in an inpatient residential psychiatric hospital ( N = 200). Results indicated that facets of sensation seeking, impulsivity, and emotion dysregulation positively predicted ever having used hallucinogens, earlier initiation of use, and lifetime use among college students. Findings also indicated that facets of sensation seeking, impulsivity, and emotion dysregulation positively predicted having ever used hallucinogens in the adolescent inpatient sample. Results highlight the need for more research on who is likely to misuse hallucinogens. If confirmed in future research, the findings presented herein indicate viable personality variables as predictors. This is especially important as there has been a recent explosion of research on the positive benefits of therapeutic hallucinogen use.